2003
DOI: 10.1152/ajplung.00308.2002
|View full text |Cite
|
Sign up to set email alerts
|

Classical isoforms of PKC as regulators of CAT-1 transporter activity in pulmonary artery endothelial cells

Abstract: Krotova, Karina Y., Sergey I. Zharikov, and Edward R. Block. Classical isoforms of PKC as regulators of CAT-1 transporter activity in pulmonary artery endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
38
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 40 publications
8
38
1
Order By: Relevance
“…A previous study indicated that melatonin decreases PKC activity in glioma cells (17), which was supported by our data showing the possible role of melatonin as a PKC inhibitor. In addition, our data are in agreement with a previous report showing that PKC-α regulates CAT-1 transport activity independent of its expression (13).…”
Section: Melatonin Regulates Pkc In Bdl Ratssupporting
confidence: 93%
See 2 more Smart Citations
“…A previous study indicated that melatonin decreases PKC activity in glioma cells (17), which was supported by our data showing the possible role of melatonin as a PKC inhibitor. In addition, our data are in agreement with a previous report showing that PKC-α regulates CAT-1 transport activity independent of its expression (13).…”
Section: Melatonin Regulates Pkc In Bdl Ratssupporting
confidence: 93%
“…It seems possible that melatonin reduces consumption of l-arginine via arginase II to increase renal l-arginine levels. Because different cell types express different members of the PKC and CAT families for the delivery of l-arginine (13,18), further study is needed to elucidate whether the protective role of melatonin on the l-arginine pathway might be due to its regulation of other PKC isoforms. Dashed lines indicate the effects of melatonin on BDL rats: melatonin inhibits protein kinase C-α (PKC-α) activity, consequently amplifying CAT-1-mediated l-arginine uptake and decreasing NADPH oxidase in the BDL liver; melatonin inhibits PKC-β activity to reduce NADPH oxidase-derived superoxide production in the BDL kidney; and melatonin reduces arginase II to increase l-arginine levels in the BDL kidney.…”
Section: Melatonin Regulates Pkc In Bdl Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…CRF binding to CRFR1 can induce PKC signaling, but at least 12 isoforms of PKC have been described (47,48). We found that PKC-e, but not PKC-βII or PKC-γ, is up-regulated in cultured primary astrocytes after CRF challenge (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…In a similar manner, it has been reported that ␣, ␤-unsaturated aldehydes, which are abundantly present in CSE, are highly reactive toward thiols, directly forming sulfhydryl-ether linkages. 32 Alternatively, protein kinase C-mediated modification of arginine transport has been demonstrated previously, 33 and CSE has been shown to activate protein kinase C in non-ECs. 34 However, we did not observe any diminution of the effects of CSE on arginine transport during coincubation with the protein kinase C inhibitor BIM-I (data not shown).…”
Section: Discussionmentioning
confidence: 87%